Meta‐Analysis of Apparent Diffusion Coefficient in Pediatric Medulloblastoma, Ependymoma, and Pilocytic Astrocytoma - Dury, Richard J.; Lourdusamy, Anbarasu; Macarthur, Donald C.; Peet, Andrew C.; Auer, Dorothee P.; Grundy, Richard G.; Dineen, Robert A. (Journal of magnetic resonance imaging, 2022)
Background Medulloblastoma, ependymoma, and pilocytic astrocytoma are common pediatric posterior fossa tumors. These tumors show overlapping characteristics on conventional MRI scans, making diagnosis difficult. Purpose To investigate whether apparent diffusion coefficient (ADC) values differ between tumor types and to identify optimum cut‐off values to accurately classify the tumors using different performance metrics. Study type Systematic review and meta‐analysis. Subjects Seven studies reporting ADC in pediatric posterior fossa tumors (115 medulloblastoma, 68 ependymoma, and 86 pilocytic astrocytoma) were included following PubMed and ScienceDirect searches. Sequence and Field Strength Diffusion weighted imaging (DWI) was performed on 1.5 and 3 T across multiple institution and vendors. Assessment The combined mean and standard deviation of ADC were calculated for each tumor type using a random‐effects model, and the effect size was calculated using Hedge's g. Statistical Tests Sensitivity/specificity, weighted classification accuracy, balanced classification accuracy. A P value < 0.05 was considered statistically significant, and a Hedge's g value of >1.2 was considered to represent a large difference. Results The mean (± standard deviation) ADCs of medulloblastoma, ependymoma, and pilocytic astrocytoma were 0.76 ± 0.16, 1.10 ± 0.10, and 1.49 ± 0.16 mm2/sec × 10−3. To maximize sensitivity and specificity using the mean ADC, the cut‐off was found to be 0.96 mm2/sec × 10−3 for medulloblastoma and ependymoma and 1.26 mm2/sec × 10−3 for ependymoma and pilocytic astrocytoma. The meta‐analysis showed significantly different ADC distributions for the three posterior fossa tumors. The cut‐off values changed markedly (up to 7%) based on the performance metric used and the prevalence of the tumor types. Data Conclusion There were significant differences in ADC between tumor types. However, it should be noted that only summary statistics from each study were analyzed and there were differences in how regions of interest were defined between studies. Evidence Level 1 Technical Efficacy Stage 3